Causes of Small and Medium Scale Enterprises Tax Evasion: A Case Study of the Informal Sector in the Accra Metropolis. - Anamoah, N.A. (University of Ghana, 2019)
This study is aimed at devising new and more effective tax enforcement strategies for the collection of taxes from informal sector in the Accra Metropolis. The research methodology involved semi-structured interviews with the Commissioner, Deputy Commissioner and Assistant Commissioner of the GRA and administering questionnaires to 385 informal enterprises in the Accra Metropolis. The findings of the study revealed that both resident and non-resident eligible persons who are either employed, have businesses, self-employed or have investments are covered by Ghana’s tax net. The strategies used to collect taxes from those in the informal sector include being provided with stickers to put on vehicles and being imprisoned for not paying taxes for those stickers; and businesses receiving visits from GRA representatives and being given invoices to pay at local tax offices. However, these efforts have been thwarted by tax offices being understaffed; inadequacy with regard to the number of computers, information technology systems, and the number of telephones, stationery and cars, the public not having enough tax education; many people not being aware that they must pay taxes; the punishment for not paying taxes being inadequate, poor legal enforcement mechanisms for tax evaders, a poorly trained tax administration, poor tax collection systems and those in charge of collecting taxes not being adequately motivated to do so. Furthermore, some other hindering factors have included informal businesses not being profitable, inadequate punishment being given for non-compliance with tax laws, citizens having a bad conscience, and citizens not trusting in the nation’s tax system.
MSc.
Keywords: Tax; Accra Metropolis